2017
DOI: 10.1016/j.chest.2016.08.1440
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Biomarkers of Collagen and Elastin Turnover Are Associated With Clinically Relevant Outcomes in COPD

Abstract: No.: ISRCTN99586989; URL: www.controlled-trials.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
(38 reference statements)
3
50
0
Order By: Relevance
“…This is in line with what is known for hepatitis and diabetes, where the SNP rs8099917 GG genotype is considered to be the risk genotype and the SNP rs12979860 CC genotype the protective genotype [35][36][37]. The IFNL3 polymorphisms predict response to treatment in patients with hepatitis C [27,30,31]. We found that the prevalence of malignancy was increased among patients with the rs8099917 GG genotype.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in line with what is known for hepatitis and diabetes, where the SNP rs8099917 GG genotype is considered to be the risk genotype and the SNP rs12979860 CC genotype the protective genotype [35][36][37]. The IFNL3 polymorphisms predict response to treatment in patients with hepatitis C [27,30,31]. We found that the prevalence of malignancy was increased among patients with the rs8099917 GG genotype.…”
Section: Discussionsupporting
confidence: 86%
“…As previously described [31], serum levels of fragments of collagen type III (C3M), fragments of collagen type VI (C6M), pro-form of collagen type III (Pro-C3) and proform of collagen type VI (Pro-C6) were measured with Nordic Bioscience assays according to the manufacturer's instructions.…”
Section: Collagen Markersmentioning
confidence: 99%
“…However, recent published report with the same biomarkers in other well-known COPD cohorts support the findings that C6M and EL-NE are significantly associated with lung function in COPD [73, 74], and have been found to be elevated during exacerbations in a smaller study [56]. …”
Section: Discussionsupporting
confidence: 60%
“…These biological processes deep within the matrix of the lung, may be associated with COPD phenotypes, disease progression, and events such as exacerbations. In direct alignment, the balance between type VI collagen formation and degradation, was shown to be significantly changed as measured by the same protein biomarkers in serum, in COPD patients with exacerbations [56, 73, 74]. Furthermore, type VI collagen remodeling as measured by these biomarkers has been associated with disease progression, defined by change in FEV 1 , and mortality in COPD patients from the ECLIPSE cohort [65].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil elastase-generated fragments of elastin (EL-NE) is different between stable and exacerbation of COPD patients. The serum level of EL-NE is associated with lung function [102]. Elastin breakdown mediated by neutrophil elastase is associated with COPD-induced inflammation [103].…”
Section: Neutrophils In Copdmentioning
confidence: 99%